A Coverage and Slicing Dependencies Analysis for Seeking Software Security Defects. (2nd April 2014) - He, Hui; Zhang, Dongyan; Liu, Min; Zhang, Weizhe; Gao, Dongmin
Abstract : Software security defects have a serious impact on the software quality and reliability. It is a major hidden danger for the operation of a system that a software system has some security flaws. When the scale of the software increases, its vulnerability has becoming much more difficult to find out. Once these vulnerabilities are exploited, it may lead to great loss. In this situation, the concept of Software Assurance is carried out by some experts. And the automated fault localization technique is a part of the research of Software Assurance. Currently, automated fault localization method includes coverage based fault localization (CBFL) and program slicing. Both of the methods have their own location advantages and defects. In this paper, we have put forward a new method, named Reverse Data Dependence Analysis Model, which integrates the two methods by analyzing the program structure. On this basis, we finally proposed a new automated fault localization method. This method not only is automation lossless but also changes the basic location unit into single sentence, which makes the location effect more accurate. Through several experiments, we proved that our method is more effective. Furthermore, we analyzed the effectiveness among these existing methods and different faults.